Nutrition labels of foods: friends or foes in public health? Critical vulnerabilities of U.S. FDA Nutrition Facts label and invention of a reliable Nutrition Facts label - Abed Forouzesh; Fatemeh Forouzesh; Sadegh Samadi Foroushani; Abolfazl Forouzesh (Food Production, Processing and Nutrition)
Abstract Nutrition labels on packaged foods or on shelf tags are used to help the general population make informed food choices to reduce or prevent diet-associated chronic diseases and meet nutritional needs. However, inaccurate nutrition labeling can mislead consumers by providing unsuitable nutritional assessments, which can elevate the risk of certain chronic diseases and cause huge medical costs. A study of 8,596 foods from the National Nutrient Database of the U.S. Department of Agriculture (USDA) revealed that only 0.2% of foods are customarily consumed 100 g or 100 mL per eating occasion. Thus, it is not reasonable to provide nutrient information based on 100 g or 100 mL on nutrition labels. Despite the fact that providing nutrient information based on 100 g or 100 mL on nutrition labels is an incorrect approach, unfortunately, most of the nutrient regulations in the world are based on 100 g or 100 mL. The Nutrition Facts label regulated by the U.S. Food and Drug Administration (FDA): (1) cannot make a significant contribution to the prevention or reduction of obesity and overweight; (2) makes food choices difficult and time-consuming; (3) helps consumers choose some foods containing excessive energy; (4) helps consumers choose some foods high in negative nutrients (including energy/calories, trans fat, saturated fat, sodium, cholesterol, sugars, and fat); (5) discourages consumers from choosing some foods low in negative nutrients; (6) helps consumers choose foods high in trans fat or saturated fat and low in cholesterol; (7) helps consumers choose some small serving foods high in negative nutrients; (8) discourages consumers from choosing some nutritious foods; (9) eliminates the ability of consumers to monitor their intake of many positive nutrients and to identify and compare foods in terms of many positive nutrients; (10) encourages unsuitable or excessive uses of fortification; and (11) promotes fortified foods and degrades unfortified foods. The proposed Nutrition Facts label helps individuals who desire to comply with dietary recommendations from health care providers or public health guidance. The proposed Nutrition Facts label is an accurate, convenient, and quick information tool for making informed food choices to reduce or prevent diet-associated chronic diseases and to meet nutritional needs in the context of daily energy needs. Graphical Abstract